How Individuals with ME/CFS Are Referred to in Medical Research: A Content Analysis of Identity-First and Person-First Language - Yousif, Razan; Jason, Leonard (Utan Kayu Publishing, 2026)
This study examined the use of person-first and identity-first language in published Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) medical research articles. Person-first language emphasizes the individual before their condition (e.g., “person with diabetes”), whereas identity-first language foregrounds the condition (e.g., “diabetic”). Because language has been discussed as a potential contributor to stigma in some chronic illness and disability contexts, documenting language patterns in the scientific literature may provide insight into how individuals are represented. The current study analyzed how individuals with ME/CFS were described in a sample of 85 medical research articles. Across these articles, references to individuals with ME/CFS appeared 3,211 times. Identity-first language was the most frequently used form of terminology (61.9%), followed by person-first language (22.9%) and other descriptors (15.2%). Most articles (72.9%) used both identity-first and person-first language. These findings highlight prevailing linguistic patterns in the ME/CFS research literature and underscore the importance of continued examination of language use in scientific communication.